ChemInform Abstract: Encapsulated Cobalt—Porphyrin as a Catalyst for Size‐Selective Radical‐Type Cyclopropanation Reactions. Issue 41 (7th October 2014) - Otte, Matthias; Kuijpers, Petrus F.; Troeppner, Oliver; Ivanovic‐Burmazovic, Ivana; Reek, Joost N. H.; de Bruin, Bas
Abstract A supramolecular cage catalyst, generated by encapsulation of Co(tetra(4‐pyridyl)porphyrin) into a Nitschke‐type M8L6 cubic cage is utilized in these reactions.